A Schumpeterian Model of Duopolistic Competition - Guido Giacomo Preparata; Giuliano Preparata (Review of Business and Economics Studies, 2022)
Aim. This paper models the dynamics of technological change through the competitive interaction of two firms. The duopolists strive to outperform each other by exploiting the two fundamental Schumpeterian forces of economic development: innovation and imitation. method. By extending over a number of periods a technological “limit-pricing model” (whereby the “learning-by-doing effect” is the source of the barrier to entry) and assuming that the two firms compete following one another in the role of innovator and imitator. As result, it is possible to trace out the paths followed by the market shares of both producers and to derive endogenously a unit cost curve characterizing the industry in the long run. conclusion. A further merit of the model presented herein is its representation of a “micro-macro transition phase” — viz., the passage from individual practice to industrial standard — through a simplified but, nonetheless, realistic depiction of behavioural routines.